Information and communication technology availability, access and use by Agricultural Extension Agents and Farmers in Dangme East Region - Adjoe, C.; Freeman, C.K.; Boateng, S.D. (Journal of Ghana Science Association, 2010)
Ghana’s agricultural extension has not experienced substantial chance in its mode of information dissemination. This study seeks to examine the extent of access and use of Information and Communication Technologies (ICTs) by Agricultural Extension Agents (AEAs) and farmers and how they harness their potentials in their agricultural activities. Dangme East District in South-East Ghana was purposively selected for this study. A multi-stage cluster sampling procedure was used to randomly select 120 small scale farmers and 21 AEAs from three villages in the three agricultural zones in the district. Data was collected using structured questionnaires and focus group discussions. Results showed that apart from computer and Internet which were not available, all AEAs and most farmers have personal access to mobile phone, television and radio which they use to source and communicate agricultural information. However, for decisions with regard to production, input acquisition up to marketing of farm produce, farmers to a large extent depend more on non-ICT sources. On the other hand, for meteorological information, farmers depend more on radio, television and mobile phone. There was significant relationship p=(0.00) and 0.042) between farmers extent of access to mobile phone and radio and its use in agricultural activities. Also, there was s significant different p=(0.03) between extents of access to T.V. and how often farmers used it in their agricultural activities. There is a great scope and potential for agricultural extension service to explore the use of television, radio and mobile phone to enhance farmers’ access to timely agricultural information.
Keywords: Communication Technology